2006
DOI: 10.1364/oe.14.012485
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact laser spectroscopy for plant discrimination in terrestrial crop spraying

Abstract: Abstract:The early development of a novel micro-photonic based sensing architecture for use in selective herbicide spraying systems performing noncontact spectral reflectance measurements of plants and soil in real time has been described. A combination module allows three laser diodes of different wavelengths to sequentially emit identically polarized light beams through a common aperture, along one optical path. Each exiting beam enters an optical structure which generates up to 14 parallel laser beams. A pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Replacing the existing control system with embedded hardware would reduce this minimum leaf size to approximately 6mm at vehicle speed of 36km/h. Previous static results, [5], showed that the weed sensor is also capable of limited discrimination of green plants. These capabilities make the weed sensor suitable for plant discrimination when mounted on a farming vehicle.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Replacing the existing control system with embedded hardware would reduce this minimum leaf size to approximately 6mm at vehicle speed of 36km/h. Previous static results, [5], showed that the weed sensor is also capable of limited discrimination of green plants. These capabilities make the weed sensor suitable for plant discrimination when mounted on a farming vehicle.…”
Section: Resultsmentioning
confidence: 98%
“…The physiological differences between plant species are evident in the spectral region from 400nm to 800nm. The prototype weed control sensor described in this paper is capable of limited plant discrimination ("green from green") using laser sources at three selected wavelengths within this region [5]. Experimental results are shown for detection of green leaves of Spathiphyllum at simulated vehicle speeds of 7 and 22 km/h.…”
Section: Introductionmentioning
confidence: 99%
“…Two optical sensors were independently evaluated: a line scan camera [2,3] and an alternative linear sensor array. The line scan camera has 1024 pixels of size 14 × 14µm, 12 bit resolution and line rate of up to 68kHz.…”
Section: Image Sensorsmentioning
confidence: 99%
“…Comprehensive spectral measurements show that the physiological differences between plant species are evident in the spectral region from 400nm to 800nm. The prototype weed control sensor described previously [4,5] uses 635nm, 685nm and 785nm laser sources and it is capable of limited plant discrimination ("green from green"). Using more wavelengths at points in the spectrum where plants show different optical characteristics in terms of reflected intensity allows more precise plant discrimination [6].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described [4,5], the output laser beam from the laser combination module passes through the custom fabricated multi-spot beam generator used for sample illumination in the plant detection system, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%